Shopping for fresh food online during Covid-19 in Shanghai - Kim Janssens; Janjaap Semeijn (The Central European Review of Economics and Management (CEREM), 2023)
Aim: The main goal is to examine the role of perceived risk in determining customers' willingness to purchase fresh food online. Research methods: Data were collected through an online survey. Respondents were recruited via a call on online platforms. A total of 287 fresh food e-commerce consumers participated. Conclusions: The results showed that perceived risk of COVID-19 infection had a positive effect on purchase intention, perceived risk of purchase behavior had a negative impact on purchase intention, and attitude was a mediating variable between perceived risk and purchase intention. Past experience moderated the relationship between perceived risk of purchase behavior and attitude. Actual consumer behavior was explained directly by purchase intention Originality: Next to attitude, subjective norms, and perceived behavioral control, the effects of perceived risk of COVID-19 infection, perceived risk of purchase behavior, and past experience on purchase intention and actual behavior to purchase fresh food online were examined in an extended Theory of Planned Behavior model. Previous studies measured overall risk perception as risk perception associated with purchase behavior and risk perception related to Covid-19 infection. The influence of both types has rarely been examined distinctively. Implications: Retailers can contribute to lowering consumers' risk perception of purchasing fresh food online and offer creative promotions to attract repeat purchases. Limitations: Only attitude correlated significantly with purchase intention, implying that additional variables may influence purchase intention. Also, although the influence of past experience is considered, a detailed distinction was not made.
Keywords: D01; D81; 330; Theory of Planned Behavior; fresh foode-commerce; perceived risk; purchase intention; past experience; Covid-19